Konsep Budaya Organisasi Dan Indikator Anggota Organisasi: Tinjauan Literatur - Paryati .; Salsabila .; Andika .; Ansori . (CV. ITTC INDONESIA, 2026)
This study analyzes the concept of organizational culture and indicators of organizational members in shaping work behavior, improving effectiveness, and strengthening teamwork.. The sources include academic books, peer-reviewed articles, and scientific publications related to organizational culture, organizational effectiveness, member behavior, participation, and responsibility. The analysis was conducted thematically through concept identification, theme classification, synthesis, and practical implication formulation. The findings show that organizational culture is a system of values, norms, artifacts, and basic assumptions that guide member behavior. A strong organizational culture clarifies work standards, strengthens a sense of belonging, improves communication, and encourages collaboration. Key indicators of organizational members include participation, responsibility, discipline, communication, teamwork, commitment, and adaptability. The discussion emphasizes that organizational culture must be consciously managed by leaders and internalized through policies, role modeling, routines, and performance evaluation. In conclusion, organizational culture is a strategic instrument for shaping member quality and organizational success, especially in educational and social organizations.